Pan-Cancer Integrated Analysis Identification of SASH3, a Potential Biomarker That Inhibits Lung Adenocarcinoma Progression - Chen, Xi; Yuan, Yixiao; Ren, Wenjun; Zhou, Fan; Huang, Xiaobin; Pu, Jun; Niu, Xiaoqun; Jiang, Xiulin (Frontiers in Oncology, 2022)
Sterile alpha motif (SAM) and Src homology-3 (SH3) domain-containing 3 (SASH3) is an adaptor protein expressed mainly in lymphocytes, and plays significant roles in T-cell proliferation and cell survival. However, its expression level, clinical significance, and correlation with tumor-infiltrating immune cells across cancers remain unclear. In this study, we comprehensively examined the expression, dysregulation, and prognostic significance of SASH3, and the correlation with clinicopathological parameters and immune infiltration in pan-cancer. The mRNA and protein expression status of SASH3 were determined by TCGA, GTEx, and UALCAN. Kaplan–Meier analysis utilized the prognostic values of SASH3 in diverse cancers. The association between SASH3 expression and gene mutation, DNA methylation, immune cells infiltration, immune checkpoints, tumor mutation burden (TMB), and microsatellite instability (MSI) were analyzed using data from the TCGA database. High expression of SASH3 was not only linked to poor OS in ESCC, LAML, LGG, and UVM, but also associated with better OS in CESC, HNSC, LUAD, SARC, SKCM, THYM, and UCEC. As for DSS, a high level of SASH3 correlated with adverse DSS in ESCC, LGG, and UVM, and lowly expressed SASH3 was associated with shorter OS in CESC, HNSC, LUAD, SARC, SKCM, and UCEC. The results of Cox regression and nomogram analyses confirmed that SASH3 was an independent factor for LUAD prognosis. Gene Ontology (GO), the Kyoto Encyclopedia of Genes and Genomes (KEGG), and gene set enrichment analysis (GSEA) results showed that SASH3 was involved in natural killer cell-mediated cytotoxicity, Th17 cell differentiation, PD-L1 expression and PD-1 checkpoint pathway in cancer, NF-kappa B signaling pathway, B-cell receptor signaling pathway, and Toll-like receptor signaling pathway. SASH3 expression was correlated with TMB in 28 cancer types and associated with MSI in 22 cancer types, while there was a negative correlation between SASH3 expression and DNA methylation in diverse human cancer. The high DNA methylation level of SASH3 was correlated with better OS in KIRC and UVM, and associated with poor OS in SKCM. Moreover, we uncover that SASH3 expression was positively associated with the stroma score in 27 cancer types, the microenvironment score, and immune score in 32 cancer types, 38 types of immune cells in 32 cancer types, the 45 immune stimulators, 24 immune inhibitors, 41 chemokines, 18 receptors, and 21 major histocompatibility complex (MHC) molecules in 33 cancer types. Finally, forced SASH3 expression inhibited lung adenocarcinoma (LUAD) cell proliferation and cell migration. Our findings confirmed that SASH3 may be a biomarker for the prognosis and diagnosis of human cancer.